种时效温度控制高温合金GH141应力变化的工艺 (2018)
本发明涉及种时效温度控制高温合金GH141应力变化的工艺，属于高温合金的热处理技术领域。其特征是：在Gleeble-3500热模拟实验机上模拟试样的焊接过程。在温度下降过程中加入了个沿轴向均匀加载的载荷，得到个相当于存在残余应力且受过焊接热冲击的热影响区。然后模拟焊后固溶、次时效和二次时效过程，经1050～1080℃固溶处理后，分别进行两级时效热处理，先进行次时效处理，在960℃保温600s，然后以10℃/s冷却到760℃，保温1800s作为二次时效，最后以10℃/s冷到室温。在热处理过程中记录应力的实时变化过程。通过本发明工艺便于得到数值小且平稳的应力，减小时效裂纹的产生概率。 The invention relates to a process for controlling the stress change of high-temperature alloy GH141 through aging temperature and belongs to the technical field of heat treatment of the high-temperature alloy. The process is characterized in that the welding process of a sample is simulated on a Gleeble-3500 heat simulation experiment machine; a load evenly loaded in the axial direction is added during temperature fall, and a heat affected zone equivalent to a zone which has residual stress and is subjected to welding heat shocks is obtained. Then post-welding dissolution treatment and primary aging and secondary aging processes are simulated, after 1,050-10,80 DEG C solution treatment, two levels of aging heat treatmen